Alcohol consumption patterns and attitudes toward alcohol, alcoholism, and alcoholics in mexican nurses - Francisco Adrián Morales-Castillo; Alejandro Torres-Reyes; Divani de Vargas; Margarita Antônia Villar-Luis; Erika Gisseth León-Ramírez; Mayra Samira De León-Ramírez; María Luz De Ávila-Arroyo; Inés Tenahua-Quitl (Universidade do Estado de Mato Grosso, 2021)
Objective: to verify the association between patterns of alcohol consumption and attitudes toward alcohol, alcoholism, and alcoholics in nurses. Method: this was a cross-sectional, correlational study with a non-probabilistic sample of professional nurses (n=163) who completed the scale of attitudes to alcohol, alcoholism and alcoholics and the Alcohol Use Disorders Identification Test. Results: attitudes were negative (cutoff point <2.4), and a negative relationship was identified between attitudes to alcohol, alcoholism and alcoholics score and alcohol consumption (r=−.013, p=.868). Conclusion: the consumption patterns for the nurses were sensible. In particular, the Mexican nurses showed negative attitudes towards alcohol-related problems, alcoholism, and alcoholics.